Efficient Cementing of CH3NH3PbBr3 Nanoparticles to Upconversion Nanoparticles Visualized by Confocal Microscopy. (20th May 2016) - Francés‐Soriano, Laura; Gonzalez‐Carrero, Soranyel; Navarro‐Raga, Enrique; Galian, Raquel E.; González‐Béjar, María; Pérez‐Prieto, Julia
Abstract : Upconversion‐perovskite nanohybrids are prepared by assembling CH3 NH3 PbBr3 perovskite nanoparticles (PK) with naked NaYF4 :Yb 3+, Tm 3+ nanoparticles (UCn ) via an innovative strategy consisting of using cucurbit[7]uril (CB[7]) to anchor the perovskite nanoparticles firmly and closely to the upconversion nanoparticles, thus leading to UCn @PKCB nanohybrids. A commercial multiphoton laser scanning confocal microscope is used to demonstrate the successful assembly. This technique proves to be useful to evaluate luminescence lifetime in the range of several tens of μs and allows visualization of the extraordinarily efficient nontrivial resonance energy transfer from the upconversion nanoparticle to the perovskite after near‐infrared (NIR) excitation of the nanohybrid as well as the homogeneity of the UCn @PKCB sample. The considerable photostability of the perovskite in these nanohybrids is demonstrated by prolonged irradiation of the nanohybrid under UV light as well as under NIR light. Abstract : Upconversion and perovskite nanoparticles are efficiently assembled by using the portals of cucurbit[7]uril to anchor the nanoparticles firmly and closely, as shown by the energy transfer efficiency to the perovskite nanoparticle after near‐infrared excitation of the nanohybrid. A commercial multiphoton laser scanning confocal microscope allows the evaluation of the assembly and the verification of the homogeneity of the sample.